Information asset as property: a legal perspective - Zulhuda, Sonny; Ansari, Abdul Haseeb (Satyam Law International, 2014)
The way people today store, reformulate and process information – and eventually generate revenues out of it, had marked the shift from a raw material-based and labor-exploiting business to the information and knowledge-based entrepreneurship. Information is increasingly becoming a commodity instead of just a business process tools. This paper attempts to revisit the notion of information as an asset and to analyze how law responds to this development. The first part seeks to reconfirm that information is the new big thing in today’s business that is characterized by globalization, digitization and deregulation of rules. The second describes and analyzes how the law –notably at the judges’ hands– contributes to the strengthening of this notion by tendency to recognize the proprietary status of information – something that is not so well established just yet. The paper argues that the law is in a changing mode towards a more information age-friendly one.